Transit time of epithelial cells in the small intestines of germfree mice and ex-germfree mice associated with indigenous microorganisms. - Savage, D C (1981)
Germfree mice housed in isolators under controlled environmental and nutritional conditions were associated with an intestinal microflora. These associated animals and germfree mice drawn from the same population were tested for the rate at which the epithelial cells transited from the crypts of Lieberkuhn to the tips of the villi in their small intestines. The method for estimating the rate of transit of epithelial cells involved the use of liquid scintillation counting to determine the amount of radioactivity entering the cells while the animals were being injected with [3H]thymidine and statistical analysis of th data with a computer program developed for the purpose. As estimated by that method, the cells transited from the crypts to the villous tips in germfree mice in about 115 h and in the associated animals in about 53 h. In monoassociated mice, a strain of a Lactobacillus sp. had no effect on the transit time of the epithelial cells. A strain of Torulopsis pintolopesii stimulated uptake of 3[H]thymidine by the small bowel mucosae in mice monoassociated with the organisms for 5 weeks. In animals monoassociated with the yeast fo 3, 4, and 6 weeks, however, the radioactive compound was incorporated into the bowel mucosae to the same extent as the mucosae of germfree mice. Therefore, similarly to the Lactobacillus strain, T. pintolopesii has no obvious influence on the transit rate of small bowel epithelial cells.